Colorado water, September/October 2009 - Schmidt, Laurie, editor; Colorado Water Institute, publisher (Colorado State University. Libraries, 2009)
Newsletter of the Water Center of Colorado State University. Theme: Urban water.
The newsletter is devoted to enhancing communication between Colorado water users and managers and faculty at the state's research universities.
Keywords: Water resources development -- Colorado; Water use -- Colorado; Water-supply -- Colorado; Water-supply -- Management -- Colorado